مصحف مسجد النور المخطوط دراسة وصفية نقدية-الربع الأول أنموذجا- - مسيف نوال (University of Eloued جامعة الوادي, 2024)
"هذه الدِّراسة بعنوان ""مصحف مسجد النُّور المخطوط - دراسة وصفيّة نقديّة – الرّبع الأوُّل أُنموذجا"" تَضمَّنت الإجابة عن الإشكاليَّة العامَّة الَّتي كانت كالآتي: هل يمكن لمصحف ""مسجد النُّور المخطوط"" أن يُبرز الظَّواهر العلميَّة والتَّاريخيَّة لعلوم المصاحف ويكشف لنا اختيارات مُهمِّة غابت في مصاحفنا المعاصرة؟ وقد حُصِرت الإجابة عنها في أربعة مباحث: تناول المبحث الأول أهميَّة المصاحف المخطوطة بصفة عامة، والتعريف بالمصحف المدروس وخصائصه الفنيَّة. وكان الثَّاني والثَّالث والرَّابع لدراسة النَّواحي التَّطبيقيّة للمصحف المخطوط، وجاءت وفْقَ قواعد علوم المصاحف "" علم الرَّسم العثماني، الضَّبط، العدّ، التَّجزئة والتَّحزيب، فواتح السُّور، المكيِّ والمدنيَّ، الوقف والابتداء"". وأهمّ النَّتائج الَّتي توصلت إليها هي: 1 - ظهور تاريخ كتابة المصحف في أجزائه، الَّذي كان فجر 16 ربيع الآخر سنة 1317ه ما يوافق في التَّقويم الميلادي بين سنتي 1899م و1900م. 2 - لقد اتَّسَمَ المصحف المخطوط بالخصائص الكتابيَّة للرَّسم العثماني، وتميَّز باختيار مذهب أبي داود في المسائل الخلافيَّة، وأبدى التَّوافق شِبه التَّام لعمل المغاربة، كما أكَّد المعلومات النَّظرية المتداولة عن اختيارات بعض العلماء التي شاعت في ذلك العصر؛ كالنَّقط المدور لعلامة الهمز، واستعمال الشَّدة حرف الدَّال؛ الَّذي هو آخر كلمة شديد، وظهور مذهب أهل العربيّة في علامة السُّكون التي هي حرف الهاء، كما أثبت انتشار رواية ورش عن نافع المدنيّ في بلادنا الجزائر في تلك الحقبة. وفي الأخير ذكرت بعض التَّوصيات أهمها: ضرورة العناية بالمخطوطات، ، وفي مقدمتها المصاحف المخطوطة، فهو مجال يحتاج إلى تنسيق الجهود، وعمل مؤسّسي ينهض بهذه المهمَّة ويسهِّل وصول الباحثين إليها.""This study, entitled “The Manuscripts of the Al-Nour Mosque - A Critical Descriptive Study - The First Quarter as a Model,” included an answer to the general problem, which was as follows: Can the “Al-Nour Mosque Manuscripts” highlight the scientific and historical phenomena of the Qur’anic sciences and reveal to us important choices that are absent in our contemporary Qur’ans? The answer to it was limited to four sections: The first section dealt with the importance of manuscript Qur’an in general, and the definition of the studied Qur’an and its artistic characteristics. The second, third and fourth were to study the applied aspects of the manuscripts of the Qur’an, and were in accordance with the rules of Qur’anic sciences: “the science of Uthmani drawing, exactness, counting, division and division, opening surahs, Meccan and Medinan, stopping and beginning.” The most important results I reached are: 1 - The date of writing the Qur’an appeared in its parts, which was the dawn of Rabi’ al-Akhir 16 in the year 1317, which corresponds in the Gregorian calendar to the years 1899 AD and 1900 AD. 2 - The manuscript Qur’an was characterized by the written characteristics of the Ottoman script, and was distinguished by the choice of Abu Dawud’s doctrine in controversial matters. It showed almost complete agreement with the work of the Moroccans. It also confirmed the theoretical information circulating about the choices of some scholars that were widespread in that era. Such as the rounded dot for the hamza sign, and the use of the shaddah letter dal; Which is the last word of Shadeed, and the emergence of the doctrine of the people of Arabic in the sign of sukun, which is the letter Ha, as proven by the spread of Warsh’s narration on the authority of Nafi’ al-Madani in our country, Algeria, in that era. Finally, I mentioned some recommendations, the most important of which are: the necessity of caring for manuscripts, especially manuscripts of the Qur’an, as this is an area that requires coordination of efforts and institutional work that carries out this task and facilitates researchers’ access to them"
Keywords: مصحف، مسجد النور، مخطوط، الوادي; mushaf; Nour Mosque; manuscript; el oued.